تداخل جدولة التمرين المتسلسل الثابت وباستخدام بعض الأدوات المساعدة في الأداء الفني السباحة الحرة للطالبات - صالح, زانا محمد محمد; خدر, بيخال حسين (Sulaimani Journal for Humanities, 2022)
Aims of the Research: Identifying the impact of the educational curriculum using some auxiliary tools on technical performance and the trend towards swimming for female students. 2. Recognizing the impact of the approach used in learning artistic performance and the trend towards swimming for female students. 3. Recognizing the preference for the impact of the educational curriculum using some auxiliary tools and the method used in technical performance and the tendency towards swimming among students. The Researcher’s Collected Works: The researcher used the experimental method because it is related to the nature of the research, while the research sample consisted of female students of the Sports Institute for the first academic year at the Institute of Physical Education in Rania Region. The researcher absorbed a number of devices, tools, means of collecting information, a questionnaire, tests and measurements to reach the research objectives. Swimming, and where the final experiment was conducted in a closed swimming pool Rania, and to process the data, the researcher used statistical means (arithmetic mean, standard deviation, deviation coefficient, T-test for the two correlated samples, percentage). The statistics were conducted using the statistical program (SPSS). In conclusions: 1- The overlap of the educational curriculum with the fixed sequential exercise using some auxiliary tools had a positive effect on the students' technical performance and the tendency towards swimming. 2- The educational curriculum followed had a positive impact on the technical performance and the tendency towards swimming among the female students. 3- The experimental group that used sequential and static exercises and some auxiliary tools outperformed the control group in technical performance and orientation towards swimming among the students.